Management of an electric vehicle charging system supported by RES and storage systems - Fernao Pires, Vitor (2018)
It is predicted to the near future that electric vehicle (EV) charging systems will have an important impact on the electric infrastructures. Thus, in order to contribute to a sustainable world, the use of renewable energy sources (RES) will play an important role to generate the required energy to the EVs. However, in order to optimize the global electrical efficiency, the RES should be placed as near as possible to the EVs charging systems. On the other hand, to provide stability to the system, energy storage systems, such as batteries and supercapacitors should also be considered. Under this context, this paper presents an EV charging system supported by RES and a storage system (supercapacitors and batteries). It will be presented the management of the storage systems, as well, an overall controller to stabilize the DC voltage bus. Several modes of the charging system operation will be presented. It also be presented results of the overall system showing the effectiveness of the proposed algorithms.